Introduction to LeadershipLAB: A Competency Based Executive Development Program - Ginting, Henndy (ANIMA Indonesian Psychological Journal, 2009)
This paper aims to introduce Leadership Laboratory (LeadershipLAB) as a new idea to improve current executive development approaches in industries and organizations. LeadershipLAB is a combination of the assessment centre (AC) program and discussion of the assessment results during feedback sessions, which were done repeatedly in a controlled situation to enhance the managerial competencies of the participants. The paper will first explain the course of actions in the LeadershipLAB such as general preview of the related competencies, conducting simulations and interview sessions, delivering general as well as individual feedback sessions, and writing individual progress reports. Then it will be completed by a case study on the 2nd and 3rd managerial level in a local government organization in Indonesia. The top leadership’s trust in using the LeadershipLAB was quite high and participants who showed progress in the LeadershipLAB tend to stay in their current position or rise to a higher position. Tulisan ini bermaksud memperkenalkan Laboratorium Kepemimpinan (LeadershipLAB) sebagai sebuah gagasan baru untuk memperbaiki berbagai metode pengembangan eksekutif saat ini. LeadershipLAB merupakan kombinasi dari program Assessment Centre (AC) dan mengonsultasikan hasilnya dengan partisipan melalui sesi-sesi balikan. Proses ini dilakukan berulang dalam situasi terkontrol untuk meningkatkan kompetensi manajerial mereka. Pertama-tama tulisan ini akan menjelaskan langkah-langkah tindakan di dalam LeadershipLAB seperti pembahasan umum tentang kompetensi yang berkaitan dengan target jabatan, melakukan simulasi dan sesi-sesi wawancara, menyampaikan balikan baik secara umum maupun individual serta menyusun laporan perkembangan partisipan yang dilakukan oleh assessor terlatih. Selanjutnya artikel ini akan dilengkapi dengan studi kasus pada eselon 2 dan 3 di salah satu organisasi pemerintahan kabupaten di Indonesia. Keyakinan pimpinan puncak (bupati dan jajarannya) akan hasil LeadershipLAB tergolong cukup tinggi. Partisipan yang menunjukkan perkembangan pada LeadershipLAB cenderung bertahan pada jabatannya atau dipromosikan ke jabatan yang lebih tinggi.